(untitled) (Atti del Sodalizio Glottologico Milanese, 2021)
This paper investigates the lexicalization pattern of motion events in Aymara, an Andean language spoken in Bolivia, Peru, and Chile. After providing a description of the morphosyntax of translational motion events, this study aims at a preliminary typological classification of Aymara within the framework of Talmy’s typology (Talmy 2000). With this purpose, three diagnostic tests have been used to determine the basic framing-typology of motion events. These tests consider i) the size of manner-of-motion lexicon and, more broadly, the degree of manner salience, ii) the complex-path constructions and the use of ‘plus-ground’ clauses, iii) the expression of boundary-crossing. The results of this analysis are in line with predictions of expected values according to Talmian typology, and suggest that Aymara is a predominantly satellite-framed language.